EFFECTIVENESS OF SAFETY RIDING EDUCATION METHODS AND MEDIA TO ADOLESCENT IN JEMBER REGENCY - Farida Wahyu Ningtyias; Iken Navikadini; Afif Hamdalah; Irfan Rifai; Trianti Dewi Kencana Wungu (Journal of Indonesia Road Safety, 2020)
Traffic accidents are the third largest killer in the world under coronary heart disease and tuberculosis. Based on the Indonesia Transportation Outlook, there are four factors that cause accidents, namely the condition of transportation infrastructure, human factors, and nature. However, human negligence is a major factor causing the high number of traffic accidents. Research on the feasibility and effectiveness of methods and educational media for riding safety programs for teenage motorbike users needs to be done. The study was conducted in Jember Regency in four schools which were divided into schools that received intervention on safety riding and not. The results show the method used in the form of counseling with the help of media in the form of power points. There is no difference in attitudes and actions between groups that get intervention and not. However, there are a small number of groups that do not get an intervention that has a bad attitude and behavior. Safety riding counseling at school can increase knowledge so that it is expected to provide behavioral changes to students to drive safely. Kecelakaan lalu lintas merupakan pembunuh ketiga terbesar di dunia di bawah penyakit jantung koroner dan tuberculosis. Berdasarkan Outlook Transportasi Indonesia, terdapat empat faktor penyebab kecelakaan, yakni kondisi sarana prasarana transportasi, faktor manusia, dan alam. Namun demikian, kelalaian manusia menjadi faktor utama penyebab tingginya angka kecelakaan lalu lintas. penelitian mengenai kelayakan serta efektivitas metode dan media edukasi program safety riding pada remaja pengguna motor perlu dilakukan. Penelitian dilaksanakan di Kabupaten Jember pada 4 sekolah yang terbagi menjadi sekolah yang mendapatkan intervensi tentang safety riding dan tidak. Hasil menunjukkan metode yang dipakai berupa penyuluhan dengan bantuan media berupa power point. Tidak ada perbedaan sikap dan tindakan antara kelompok yang mendapatkan intervensi dan tidak. Namun kelompok yang tidak mendaptkan intervensi ada sebagian kecil yang memiliki sifat dan tindakan yang buruk. Penyuluhan safety riding di sekolah dapat meningkatkan pengetahuan sehingga diharapkan bisa memberikan perubahan perilaku pada siswa untuk aman berkendara.